Randomized trials published by institutions located in Peru: bibliometric study from the period 2000 to 2022 - Triveño Torres, Melody Alessandra (2023)
Objetive: To characterize the scientific production of randomized trials by institutions located in Peru from January 1, 2000 to December 30, 2022. Materials and methods: Bibliometric study, two databases (MEDLINE and SciELO) were reviewed. Original articles were included in which at least one author stated an institution located in Peru as affiliation. Scientific production was characterized according to: thematic area, participation of institutions located in Peru, scientific journals in which the articles were published, and approval of the studies by a Research Ethics Committee (REC). Results: A total of 402 articles were analyzed, a growing trend in scientific production was evidenced, going from six in the year 2000 to 39 in the year 2021, the predominant thematic area is infectious, the first two institutions with the highest number of randomized trials belong to the education sector, 189 (47.0%) articles were published in journals in the United States, in 37 (9.2%) articles there is no information on ethical aspects or it is not explicitly stated whether or not it was approved by a CEI. Conclusions: There is a growing trend of scientific production on this study design, the predominant thematic area is infectious, the most productive Peruvian institutions belong to the education sector, about half of the articles were published in journals in the United States, and in a tenth part of the articles do not explicitly state whether or not the study was approved by an REC.